Construction of a Turn Off-On-Off Fluorescent System Based on Competitive Coordination of Cu2+ between 6, 7-Dihydroxycoumarin and Pyrophosphate Ion for Sensitive Assay of Pyrophosphatase Activity. (27th September 2016) - Zhao, Lingzhi; Zhao, Liu; Miao, Yanqing; Liu, Chunye; Zhang, Chenxiao
Abstract : The detection of pyrophosphatase (PPase) activity is of great significance in diagnosing diseases and understanding the function of PPase-related biological events. This study constructed a turn off-on-off fluorescent system for PPase activity assay based on PPase-regulated competitive coordination of Cu 2+ between a water-soluble fluorescent probe 6, 7-dihydroxycoumarin (DHC) and pyrophosphate (PPi). The probe DHC can coordinate with Cu 2+ and consequently display on-off type fluorescence response. Furthermore, the in situ formed nonfluorescent Cu 2+ -DHC complex can act as an effective off-on type fluorescent probe for sensing PPi due to the higher coordination reactivity between Cu 2+ and PPi than that between Cu 2+ and DHC. The subsequent addition of PPase to the mixture containing Cu 2+, DHC, and PPi leads to the fluorescence requenching of the system again (an off state) because PPase catalyzes the hydrolysis of PPi into orthophosphate in the reaction system. Under the optimum conditions, the decrease of the fluorescence intensity of DHC-Cu 2+ -PPi system was linear with the increase of the PPase activity in the range from 0.1 to 0.3 U. The detection limit was down to 0.028 U PPase (S / N = 3 ). Moreover, the as-established system was also applied to evaluate PPase inhibitor. This study offers a simple yet effective method for the detection of PPase activity.